Pentacycloundecane (PCUD)‐Based Cage Frameworks as Potential Energetic Materials: Syntheses and Characterization. Issue 12 (12th November 2020) - Kotha, Sambasivarao; Cheekatla, Subba Rao; Lal, Sohan; Mallick, Lovely; Kumbhakarna, Neeraj; Chowdhury, Arindrajit; Namboothiri, Irishi N. N.
Abstract: A new variety of cage frameworks containing pentacycloundecane (PCUD) were synthesized. These compounds contain azide and triazole units. Four new cage frameworks were designed and constructed starting from easily accessible starting materials such as 2, 3‐dimethylhydroquinone, 1, 4‐dimethoxybenzene, and dicyclopentadiene using [2+2] photocycloaddition as the key step. The structures of these symmetrical cage bis‐azide and cage bis‐triazole compounds have been confirmed by single‐crystal X‐ray diffraction studies. DFT analysis at different levels of theory were used to optimize the geometries and compute the heats of formation of the title compounds. Their propulsive and explosive properties were also calculated using suitable computational methods. The thermodynamic stability of the title compounds was theoretically analysed based on their bond dissociation energies. The thermal stability was evaluated by TGA‐coupled FTIR analysis. Abstract : Pentacycloundecane (PCUD) based cage frameworks such as azides and triazoles display high heats of formation, specific impulse, and exhibit propulsive properties superior to RP1 and HTPB.